Factors affecting quality of life in children and adolescents with hypermobile Ehlers‐Danlos syndrome/hypermobility spectrum disorders. Issue 4 (31st January 2019) - Mu, Weiyi; Muriello, Michael; Clemens, Julia L.; Wang, You; Smith, Christy H.; Tran, Phuong T.; Rowe, Peter C.; Francomano, Clair A.; Kline, Antonie D.; Bodurtha, Joann
Abstract : Hypermobile Ehlers‐Danlos syndrome (hEDS) is a hereditary disorder of connective tissue, often presenting with complex symptoms can include chronic pain, fatigue, and dysautonomia. Factors influencing functional disability in the pediatric hEDS population are incompletely studied. This study's aims were to assess factors that affect quality of life in children and adolescents with hEDS. Individuals with hEDS between the ages 12–20 years and matched parents were recruited through retrospective chart review at two genetics clinics. Participants completed a questionnaire that included the Pediatric Quality of Life Inventory (PedsQL™), PedsQL Multidimentional Fatigue Scale, Functional Disability Inventory, Pain‐Frequency‐Severity‐Duration Scale, the Brief Illness Perception Questionnaire, measures of anxiety and depression, and helpful interventions. Survey responses were completed for 47 children and adolescents with hEDS/hypermobility spectrum disorder (81% female, mean age 16 years), some by the affected individual, some by their parent, and some by both. Clinical data derived from chart review were compared statistically to survey responses. All outcomes correlated moderately to strongly with each other. Using multiple regression, general fatigue and pain scores were the best predictors of the PedsQL total score. Additionally, presence of any psychiatric diagnosis was correlated with a lower PedsQL score. Current management guidelines recommend early intervention to prevent disability from deconditioning; these results may help identify target interventions in this vulnerable population.